Development of a Prototype of Android-Based Nursing Care Standards for Diabetes Mellitus Patients in the Interna Nursing Ward at RSUD Toto Kabila - Falah, Fakhriatul (Jambura Nursing Journal, 2024)
Gorontalo ranks 7th in the number of Diabetes Mellitus sufferers out of 35 provinces in Indonesia with prevalence increasing from 1.3% in 2013 to 2.4% in 2018. High prevalence and morbidity can be reduced by improving the quality of nursing care in hospitals through standardization of nursing care for diabetes mellitus patients. This research aims to develop electronic-based nursing care standards (E-SAK) and to improve the quality of nursing care for diabetes mellitus patients by conducting prototype trials. This research uses a pre-experimental design research type with a one shot case study approach where measurements of the effectiveness of the application and its level of usefulness are carried out after the intervention. The type of sampling used total sampling by taking all 30 nurses in the internal room. The nursing care standards used in this application are prepared based on nursing professional organization standards (PPNI), a list of diagnoses that form the application database using an evidence-based nursing approach based on the results of a literature review. The research instrument used in this study was the SUS (System Usability Scale) questionnaire to test the ease of use of the application by nurses. The SUS questionnaire was adapted from research conducted by (Alfatoni et al., 2020) and has gone through a reliability test with a Cronbach's Alpha value > 0.06. From the statistical test results, it was found that the average usability score was 89, which means the level of satisfaction means that this application prototype is acceptable or easy to use and the level of usefulness is high by respondents. Thus, this application can be used by hospitals to improve the quality of nursing care services for diabetes mellitus patients.